La « configuration en tiers-lieu », une mise en scène du changement social - Matei Gheorghiu (VertigO, 2021)
“Living-labs” are part of a larger family of participatory citizen approaches coined as “third-place configurations” (Burret, 2018). As their characteristics are fully analyzed here, I will bind myself to stating a few general remarks. To begin with, I would like to stress their historical context of emergence ; then, I will try to question their paradoxical common denominator : because of their quasi-institutionalized heterogeneity and instability, the social processes they embody constitute an “adapted” reflexivity device to the neo-liberal governance regime. Finally, since this work is based on ten years of action research in this context, I will allow myself to state some vigilance principles useful both to the researcher, to the practitioner or to the initiated amateur.